2019
DOI: 10.3390/ma12213562
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Aluminum-Nitride Nano-Fillers on the Mechanical, Electrical, and Thermal Properties of High Temperature Vulcanized Silicon Rubber for High-Voltage Outdoor Insulator Applications

Abstract: AlN nanoparticles were added into commercial high-temperature-vulcanized silicon rubber composites, which were designed for high-voltage outdoor insulator applications. The composites were systematically studied with respect to their mechanical, electrical, and thermal properties. The thermal conductivity was found to increase greatly (>100%) even at low fractions of the AlN fillers. The electrical breakdown strength of the composites was not considerably affected by the AlN filler, while the dielectric consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…An identical result was reported, where nano-AlN from the same manufacturer was used [29]. It is worthy to mention that many inconsistent particle size distribution between observations and the data provided by suppliers has been reported for nano-AlN, including in our previous work [11,30,31], and we suggested that this could be related to the hydrolytic instability of AlN powders. Li et al [28] reported that the morphology and particle size distribution of the AlN microparticles are significantly changed after exposure to moist air (80 RH%) for 400 h and can have a dehydration weight loss up to 20% after being heated to 500°C.…”
Section: Aln Characterisationsupporting
confidence: 80%
“…An identical result was reported, where nano-AlN from the same manufacturer was used [29]. It is worthy to mention that many inconsistent particle size distribution between observations and the data provided by suppliers has been reported for nano-AlN, including in our previous work [11,30,31], and we suggested that this could be related to the hydrolytic instability of AlN powders. Li et al [28] reported that the morphology and particle size distribution of the AlN microparticles are significantly changed after exposure to moist air (80 RH%) for 400 h and can have a dehydration weight loss up to 20% after being heated to 500°C.…”
Section: Aln Characterisationsupporting
confidence: 80%
“…SIR used for outdoor insulation materials also needs to have high resistivity, thermal conductivity and electrical strength. Adding metal oxides, nitrides and reduced graphene oxide can increase the insulation's performance [10][11][12][13]. In order to improve the electrical properties, the erosion and wear resistance of silicone rubber in the field of high-voltage insulation, SIR composites were prepared by filling them with aluminum hydroxide (ATH), irregular silica (IS), spherical silica (SS) and silicon dioxide (SiO 2 ) by mechanical blending [14][15][16].…”
Section: Introductionmentioning
confidence: 99%